2014
DOI: 10.1111/jpn.12248
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the supplementation of Bacillus subtilis RX7 and B2A strains on the performance, blood profiles, intestinal Salmonella concentration, noxious gas emission, organ weight and breast meat quality of broiler challenged with Salmonella typhimurium

Abstract: An experiment was conducted to evaluate the effects of B. subtilis RX7 and B. subtilis B2A on growth performance, blood profiles, intestinal Salmonella population, noxious gas emission, organ weight and breast meat quality of broilers under S. typhimurium challenge. A total of 120, one-day-old Ross 308 male broiler chicks were assigned to four dietary treatments, composed of six replications, with five birds per replication, for 10 day. The dietary treatment groups were negative control (NC; no antibiotic, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 32 publications
6
44
1
Order By: Relevance
“…Numerous studies have shown that birds consuming diets supplemented with B. subtilis, which is known to increase the intestinal lactic acid, have a lower incidence of Salmonella than those fed control diets (Wu et al 2009;Knap et al 2011). A recent study reported by Park and Kim (2014) showed that when 21-day-old chicks were dosed with B. subtilis B2A or B. subtilis RX7 and later challenged with S. ,SalmonellaB. subtilis showed significant differences in Salmonella population in the intestine, it has been suggested that this might be the metabolic effects of obligate spore-forming aerobes on pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have shown that birds consuming diets supplemented with B. subtilis, which is known to increase the intestinal lactic acid, have a lower incidence of Salmonella than those fed control diets (Wu et al 2009;Knap et al 2011). A recent study reported by Park and Kim (2014) showed that when 21-day-old chicks were dosed with B. subtilis B2A or B. subtilis RX7 and later challenged with S. ,SalmonellaB. subtilis showed significant differences in Salmonella population in the intestine, it has been suggested that this might be the metabolic effects of obligate spore-forming aerobes on pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that commensal or probiotic organisms prevent colonization of pathogens in the gut epithelial surface by competitive exclusion. Most of the research aimed at finding a novel B. subtilis strain which can inhibit the infectious activity of S. gallinarum in order to decrease the prevalence of Salmonella in experimentally challenged laying hens that are not necessarily showing symptoms of a disease (Knap et al 2011;Park & Kim 2014). In the current experiment, we observed a distinct effect due to the concentration of probiotic treatments administered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations